An organizational model for understanding internationalization processes - Malhotra, Namrata; Hinings, CR (Journal of International Business Studies, 2010)
We propose an organizational model for understanding internationalization processes. We argue that these processes differ with the type of organization. We compare the internationalization processes of three organization types: the mass production organization; the disaggregated production organization; and the project-based organization. Each organization type responds differently to critical elements of the internationalization process, namely, the focus of entry, the degree of presence and physical presence requirements in the foreign market, which in turn influence what modal forms are adopted as the process progresses. Consequently, we observe different approaches to resource commitment in the foreign market over time.